The effect of hearing Quran verses on reducing chemotherapy-induced nausea and vomiting in cancer patients referring to Imam Hossein Hospital - Shaghayegh Kamian; Morteza Tabatabaeefar (Shahid Beheshti University of Medical Sciences, 2019)
For downloading the full-text of this article please click here. Background and Objective: Nausea and vomiting are two common and disturbing adverse effect of chemotherapy. There are studies which have used methods or psychological aid such as music therapy to prevent or treat these events. We have evaluated the effect of hearing Quranic verses on decreasing the incidence and grade of these effects. Method: This was a single group study which evaluated 31 patients who received outpatient chemotherapy in Imam Hossein hospital. The patients received usual premedication for nausea and vomiting during two cycles of chemotherapy and they also listened to Quranic verses in one of these cycles. We filled a questionnaire using international grading system for nausea and vomiting and each case was compared with himself in the two cycles. All ethical issues were observed in this study and the researchers reported no conflicts of interest. Results: The results showed the about 35% of the patients experienced vomiting during chemotherapy, which decreased to 22% after listening to Quran (p=0.125), which was not statistically significant. Also, there was a 64% decline in the incidence of vomiting (OR=0.36, p=0.03). Listening to Quran significantly decreased the probability of higher grade of nausea in 89% of cases (OR=0.12, p<0.001). About 35.5% of the patients did not have nausea, which increased to 67.7 % after intervention. Also, half of the cases experienced lower grade of nausea in the next cycle after listening to Quran. The grade of nausea did not increase to higher grade after intervention. Conclusion: Listening to Quran could significantly decrease the incidence of nausea and vomiting. Whether these effects are due to the spiritual effect of Quran or distraction of thought during chemotherapy is not known and should be evaluated in a larger and two-grouped study. Previous studies have shown that listening to Quranic verses has positive effect, including the time when anesthesia is induced. Thus, this technique can be used for controlling the adverse effects of cancer treatment too. For downloading the full-text of this article please click here. Please cite this article as: Kamian Sh, Tabatabaeefar M. The effect of hearing Quran verses on reducing chemotherapy-induced nausea and vomiting in cancer patients referring to Imam Hossein Hospital. J Res Relig Health. 2019; 5(3):45- 58.doi:https://doi.org/10.22037/jrrh.v5i3.18592